Reported alcohol drinking and mental health problems in Hong Kong Chinese adolescents. (1st July 2016) - Huang, R.; Ho, S.Y.; Wang, M.P.; Lo, W.S.; Lam, T.H.
Highlights: Even reported less-than-weekly drinking is linked to poor mental health in Hong Kong adolescents. Reported weekly drinking is linked to emotional problems and hyperactivity more strongly in girls. Binge drinking is most strongly associated with hyperactivity among all scales. Abstract: Objective: To investigate the association between reported alcohol drinking and mental health problems in Hong Kong adolescents. Methods: In a school-based questionnaire survey in 2012-13 on 4620 Secondary one (US Grade seven) to six students (mean age 14.5, SD 1.6 years; 53.4% boys), alcohol drinking was classified as never drinking (reference), experimental, former, less-than-weekly and weekly drinking. Binge drinking was defined as drinking at least five drinks on one occasion. Mental health was assessed using the Strengths and Difficulties Questionnaire (SDQ) with five subscales (emotional symptoms, conduct problems, hyperactivity, peer relationship problems and prosocial activity) and the total difficulties score (sum of the first four subscales). Multilevel regression was used to analyse the associations of mental health problems with drinking frequency and binge drinking, adjusting for potential confounders. Results: Compared with never drinking, higher total difficulties scores were associated with less-than-weekly drinking (adjusted odds ratio AOR 1.39, 95% CI 1.01–1.91), weekly drinking (AOR 3.21, 95% CI 2.18–4.70), and binge drinking (AOR 2.18, 95% CI 1.42–3.32). Weekly drinking was most strongly associated with hyperactivity (AOR 6.27, 95% CI 1.42–3.32) among all subscales. Girls were more likely than boys to report emotional problems (AOR 3.36 vs 1.47) and hyperactivity (AOR 19.2 vs 2.31) related to weekly alcohol drinking (both P for interaction <0.05). Conclusions: In Hong Kong adolescents, less-than-weekly, weekly, and binge drinking are associated with higher risks of mental health problems based on self-reported data. Prospective studies are warranted to explore the causality between alcohol drinking and mental health problems.